PENGARUH DISIPLIN DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT. DOS NI ROHA KEDIRI - Irawan, Yudhistira; Jatmiko, Udik; Yudhia, Bagus Putra (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Every company aims to develop the company to the maximum. In order for the goals achieved to run smoothly, leaders need to pay attention to the performance of their employees. The implementation of work discipline programs, morale will help control all actions and behaviors of employees to always be within the provisions that have become regulations in the company. Based on the description above, this study aims to find out how the influence of work discipline on employee performance, how the influence of morale on employee performance, how much influence between discipline and morale simultaneously on employee performance, which of the work disciplines and morale have a dominant influence on employee performance at PT. DOS NI ROHA Kediri. From the discussion of research results, all question instruments are declared valid and reliable. The results of the analysis obtained the equation Y = 2.937 + 0.293 X1 + 0.540 X2. The R square value of 0.752 means simultaneously the influence of work discipline and morale variables on employee performance by 75% and the remaining 25% is influenced by other variables such as reward, punishment, work facilities, support from superiors and bonuses or intensive outside of salary. The results of the SPSS program processing t test show that the work discipline variable has a significance of t = 0.002 < 0.05 then there is a significant influence on employee performance variables and the morale variable has a significance of t = 0.000 < 0.05 then there is also a significant influence on employee performance variables. And the results of the F test obtained a significance value f = 0.000 < 0.05 then, together the variables X1 and X2 affect the variable Y. Morale (X2) is the most dominant influential variable, this is shown by the correlation value between work discipline (X1) of 0.293 and morale (X2) of 0.540.